Literackość korespondencji Fryderyka Chopina - Samsel, Karol (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
In some measure, in opposition to the contemporary studies on Chopin’s letters emphasising their non-literary character, the aim of this study is to point at the multifaceted literariness of the correspondence of the author of the Revolutionary Etude. One of its crucial aspects would be the intertextual one: Chopin’s letters constitute an intriguing community of style, including, above all, the schemes of Fredro-like comedy and Henryk Rzewuski’s gawęda szlachecka (nobility tale). The idea of writing in the spirit of disciplined lightness, rigour of formulating thoughts in a casual, colloquial and easy manner, as Wiktor Weintraub put it, affects Chopin’s planned skill of self-creation and autothematical procedures, always in similar styles that use humour for the purpose of making thing unusual, or even obscene. The arguments collected in the article force one to withdraw Ryszard Przybylski’s conviction about Chopin’s epistolography as representing the language “serving life” only outside of literature and literariness.